Androgen receptor expression in metastatic adenocarcinoma in females favors a breast primary - Machhi Jinobya K; Komorowski Richard A; Shidham Vinod B (Diagnostic Pathology, 2006)
Abstract Background The differential diagnosis of metastatic mammary adenocarcinoma and adenocarcinomas from other primary sites can be challenging, particularly in tumors that are poorly differentiated and negative for Estrogen/Progesterone receptors (ER/PR). With progression of disease, Androgen receptors (AR) are preserved with higher frequency than ER/PR in metastatic mammary carcinoma. This study was undertaken to evaluate the diagnostic significance of AR expression in adenocarcinoma of breast and other morphologically similar adenocarcinomas. Design Formalin-fixed paraffin-embedded tissue sections of 113 primary adenocarcinoma of various sites [breast (34, all females), lung (23, M- 6, F-17), colon (9, M-2, F-7), stomach (6, M-4, F-2), liver and bile duct (11, M-5, F-6), pancreas (7, M-2, F-5), ovary (10), endometrium (7), and cervix (6)] were immunostained with monoclonal antibody for AR. Except for well differentiated lobular carcinoma of breast (5) and bronchoalveolar carcinoma of lung (10), majority of the tumors were moderately to poorly differentiated. Tumors immunoreactive for ≥ 10% of nuclei were considered AR positive. However, AR immunoreactivity in the cytoplasm only was also recorded. Results 56% (19/34) mammary carcinoma and 20% (2/10) adenocarcinoma of ovary were positive for AR. Remaining 69 adenocarcinomas did not show nuclear immunoreactivity for AR in ≥ 10% nuclei; however, 52% (36/69) showed variable cytoplasmic immunoreactivity. Conclusion Significant proportion of mammary carcinomas and some ovarian carcinomas express AR in the nuclei of more than 10% tumor cells. If metastatic tumor with unknown primary in a female is AR positive, breast and ovary are the most likely primary sites. Cytoplasmic immunoreactivity alone without nuclear immunoreactivity for AR was non-specific for this differential diagnosis.